ROVING WASTE IN TEXTILE MANUFACTURING: GENERATION, MANAGEMENT, AND SUSTAINABLE SOLUTIONS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Roving waste constitutes a significant yet understudied stream of solid waste within the yarn manufacturing sector, impacting both economic efficiency and environmental sustainability. This study employs a mixed-methods approach to quantify roving waste generation and evaluate the efficacy of various mitigation strategies. A comprehensive waste audit was conducted over a six-month period at three large-scale spinning mills, analyzing waste from different machine types and production stages. The results indicate that roving waste accounts for approximately 3.5-5.2% of total production volume, with primary causes attributed to mechanical inefficiencies (42%), operator handling errors (31%), and raw material variability (27%). Furthermore, the implementation of an integrated waste management protocol, combining machine calibration, operator training, and in-process recycling, demonstrated a 47% reduction in waste generation and a projected annual cost saving of $18.50 per metric ton of production. The findings underscore the critical importance of proactive waste management strategies in enhancing the circularity and profitability of textile manufacturing operations.